Природно-ресурсна рента і рентні платежі: диференціація понять - Тітаренко, Г.; Тітаренко, О. (Економіка природокористування і сталий розвиток, 2020)
Актуалізовано питання розмежування понять природно-ресурсної ренти і рентного платежу. Зазначено, що рентним можна вважати лише платіж, який здійснюється з підприємницького прибутку в розмірі, що обумовлюється різницею між його нормальним рівнем і надприбутком. Зауважено, що під виглядом рентного платежу сьогодні справляється не рентна плата, а лише платіж за користування ресурсом або податок за право власності на ресурс, замість повноцінного вилучення ренти з доходів користувача. Вказано на необхідність перегляду застосовуваної в податковому законодавстві термінології, чіткого розмежування понять та, відповідно, фіскальних інструментів. In the article the issue of concepts of natural resource rent and rent payment differentiation is actualized. It is stated that rent payment can be considered only that payment, which is made from entrepreneurial profit in the amount, which is caused by the difference between its normal level and surplus. The main criteria for rent payment are the following: it is shown as part of the entrepreneur's income. If you do not expect to receive entrepreneurial income, then such a payment can not be considered as rent. Then it is only a payment for the use of a resource in an economic activity, that is, a fee (formed at a cost approach or as a result of market equilibrium mechanisms) or a levy (quasi-fiscal fiscal payment of a permissive nature, that is, a fiscal levy), or a license fee for the use of a resource; it is paid not for the fact of using the resource in economic activity, but for receiving excess entrepreneurial income for the labor and capital expended because of more favorable conditions than other entrepreneurs. If there is no such excess profit, then the rent payment cannot be considered as it does not have an excess, rent component.
It is noted that the rent payment today is a payment for the use of the resource or property rights tax, instead of fully removing the rent from the user's income. It is pointed out the need to revise the terminology used in the tax legislation, to clearly distinguish between concepts and, accordingly, fiscal instruments, such as: the fee for the special use of the resource, which is compensatory, compensatory and unconditionally paid by the natural resource for the involvement of the natural resource in its economic management and use economic purposes; the object of taxation is actually the resource (its quality, quantity), and the fact that determines the fiscal obligation is the exploitation of the resource by the user; tax, which is of a general nature and is paid by the owner of the taxable resource, whether or not the resource is used in business and income generation; rent (payment), which should be deducted from entrepreneurial profits in order to remove the income earned by an entrepreneur from his or her certain advantages over other entrepreneurs of the industry or business sector due to more favorable conditions than other business entities. Amendments to the national tax legislation need to be made to clearly define the terminology and appropriate mechanisms for applying these fiscal instruments in the economic activity of the state, which will, on the one hand, effectively tax property and apply a mechanism for levying resources to offset environmental costs, and the other is to fully remove from the entrepreneurs the rents they have earned for government purposes.